Psychometric properties of the Portuguese version of the Éxamen Geronto-Psychomoteur (P-EGP). Issue 7 (2nd July 2016) - Morais, Ana; Santos, Sofia; Lebre, Paula
ABSTRACT: Aging involves concomitant and interrelated changes in sensory, motor, and cognitive function. There is a decrease in psychomotor skills—such as balance, spatial orientation, mobility, and motor coordination—visible in increased difficulties performing daily instrumental activities (e.g., self care and domestic activities). The absence of valid psychomotor instruments for the elderly population to be used by psychomotor therapists can be identified as one of the reasons why there is a scarce research in this area. Currently, in Portugal, psychomotor therapists do not have any specific, validated scale within the psychomotor domain built and/or adapted to guide psychomotor interventions with the elderly population. Therefore, the aim of this study was the translation, adaptation, and validation of the Portuguese version of the Éxamen Geronto-Psychomoteur (P-EGP) in a population of 497 elders, aged between 60 and 99 years, with and without dementia. Results of the study are presented and discussed in terms of the reliability and validity of P-EGP. The results demonstrate that P-EGP appears to be a valid and reliable assessment of psychomotor skills for the elderly population in Portugal. Practical implications and future directions of research are also discussed.